Antibacterial Activity and Phytochemical Standardization of Rhinacanthus nasutus (White Crane) - R. Pugalvendhan, G. Prabakaran (Recent Research in Science and Technology, 2009)
Plants are the most exclusive source of drugs for the majority of the words population and plant products constitute about 25% at prescribed medicines phytochemical tests have been performed in about 5,000 and nearly 1,100 species are exclusively exploted in 80% Ayurvedic, 46% Unani and 33% Allopathi medicine. The values of the present data indicated that ethanolic extract (5.8%) and aqueous extract (6.8%) showed higher extractive values when compared to other solvents. Ethyl acetate showed the least extraction value (0.9%). At the maximum concentration tested, (250µg) the organisms showed maximum sensitivity and the leaf extract proved to be better than the antibiotic disc Chloramphenicol (30mcg) which recorded 24mm as a zone of inhibition. The promising alkaloid, Rhinacanthin has potent medicinal applications. It exhibits anti proliferate activity, antimicrobial activity against dermatophytes and inhibits platdent aggregation. In spite of it’s potential. It remains unexplored and under utilized and hence chosen for the present study.